2023
DOI: 10.3390/nu15040825
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Eight Weeks’ Very Low-Calorie Ketogenic Diet (VLCKD) on Liver Health in Subjects Affected by Overweight and Obesity

Abstract: Very low-calorie ketogenic diets (VLCKD) are widely employed in successful weight-loss strategies. Herein, we evaluated the efficacy and safety of a VLCKD on non-alcoholic fatty liver disease (NAFLD) and parameters commonly associated with this condition in overweight and obese subjects who did not take any drugs. This prospective, real-life study included thirty-three participants who followed a VLCKD for 8 weeks. NAFLD was diagnosed using transient elastography (FibroScan). Data on anthropometric measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 38 publications
3
9
0
Order By: Relevance
“…It is promising to see that the LCHF diet did not have a negative impact on liver function and even showed slight improvements in liver parameters. The results of this study are consistent with other studies, such as those conducted by Cunha et al [31], D'Abbondanza et al [21], and Rinaldi et al [32], which suggest that a very-low-carbohydrate high-fat diet may be beneficial for patients with NAFLD. The metabolic shift from carbohydrates to triglycerides as the main energy source may contribute to the reduction in liver fat accumulation, especially in overweight/obese patients with increased visceral adipose tissue.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It is promising to see that the LCHF diet did not have a negative impact on liver function and even showed slight improvements in liver parameters. The results of this study are consistent with other studies, such as those conducted by Cunha et al [31], D'Abbondanza et al [21], and Rinaldi et al [32], which suggest that a very-low-carbohydrate high-fat diet may be beneficial for patients with NAFLD. The metabolic shift from carbohydrates to triglycerides as the main energy source may contribute to the reduction in liver fat accumulation, especially in overweight/obese patients with increased visceral adipose tissue.…”
Section: Discussionsupporting
confidence: 92%
“…However, the observed decrease was not clinically relevant. The study conducted by Rinaldi et al [32] showed similar results regarding to TSH after 8 weeks of VLCKD. It is important to note that changes in TSH levels should always be interpreted in the context of thyroid function and individual patient characteristics.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Another study from 2023 also indicated that VLCKD was effective in reducing blood pressure in patients with non-alcoholic fatty liver disease (NAFLD) over an 8-week period. There was a reduction in the mean systolic blood pressure from 133.51 ± 12.86 mmHg to 123.27 ± 10.51 mmHg and the diastolic blood pressure from 81.73 ± 8.09 mmHg to 75.27 ± 7.84 mmHg [207]. In a 2022 randomized controlled trial, the ketogenic diet together with continuous positive airway pressure (CPAP) reduced systolic and diastolic blood pressure values to a greater extent (from 142.8 ± 13.…”
Section: The Ketogenic Diet and Blood Pressurementioning
confidence: 90%
“…Some extremely low-carbohydrate dietary patterns with a 10% or less carbohydrate calorie proportion, termed the ketogenic diet, have been shown to improve fatty liver. 16,17 Recently, clinical randomized controlled trials revealed that a low-carbohydrate high-fat (LCHF)-diet pattern (20%-26% energy from carbohydrates and 50%-60% energy from fats) is effective in improving hepatic steatosis and insulin resistance, which are the common pathological features in ALD. 16,18 In experimental animals, LCHF-diet has been shown to ameliorate cognitive impairment and neuroinflammation, 19 inhibit cardiac hypertrophy, 20 as well as reverse HF-diet-induced hepatic lipid accumulation and insulin sensitivity reduction in mice.…”
Section: Introductionmentioning
confidence: 99%